The Three Regularities in Development Growth, Jobs and Macro Policy in Developing Countries - Mahmood, Moazam (Springer International Publishing, 2018)
The financial crisis in advanced economies and its impact on developing countries has put the longer term agenda of development - structural transformation of countries, of their growth, jobs, poverty and distribution - on the analytic and policy backburner. Day to day management of macro fundamentals in the global economy and the labour market have consumed decision makers with faltering GDP growth, soaring unemployment, and a resurgent threat of deflation. Without understanding and addressing the structural constraints and imbalances underpinning such global problems, the world economy is doomed to experience an increasing number of crises and emerging dualisms between countries. The aim of this book is to bring back a balance to the development debate by re-focusing on the structural development challenges faced by developing countries. The book develops a coherent analytical framework supported by a large body of new empirical evidence linking three core dimensions - the structure of growth, employment, and their macro drivers. Then, for each of these dimensions and relationships a variety of effective policies are also identified and elucidated with the added granularity of country cases. .